A review of climatic controls on δ18O in precipitation over the Tibetan Plateau: Observations and simulations. (1st November 2013) - Yao, Tandong; Masson‐Delmotte, Valerie; Gao, Jing; Yu, Wusheng; Yang, Xiaoxin; Risi, Camille; Sturm, Christophe; Werner, Martin; Zhao, Huabiao; He, You; Ren, Wei; Tian, Lide; et al.
Abstract [1] The stable oxygen isotope ratio (δ18O) in precipitation is an integrated tracer of atmospheric processes worldwide. Since the 1990s, an intensive effort has been dedicated to studying precipitation isotopic composition at more than 20 stations in the Tibetan Plateau (TP) located at the convergence of air masses between the westerlies and Indian monsoon. In this paper, we establish a database of precipitation δ18O and use different models to evaluate the climatic controls of precipitation δ18O over the TP. The spatial and temporal patterns of precipitation δ18O and their relationships with temperature and precipitation reveal three distinct domains, respectively associated with the influence of the westerlies (northern TP), Indian monsoon (southern TP), and transition in between. Precipitation δ18O in the monsoon domain experiences an abrupt decrease in May and most depletion in August, attributable to the shifting moisture origin between Bay of Bengal (BOB) and southern Indian Ocean. High‐resolution atmospheric models capture the spatial and temporal patterns of precipitation δ18O and their relationships with moisture transport from the westerlies and Indian monsoon. Only in the westerlies domain are atmospheric models able to represent the relationships between climate and precipitation δ18O. More significant temperature effect exists when either the westerlies or Indian monsoon is the sole dominant atmospheric process. The observed and simulated altitude‐δ18O relationships strongly depend on the season and the domain (Indian monsoon or westerlies). Our results have crucial implications for the interpretation of paleoclimate records and for the application of atmospheric simulations to quantifying paleoclimate and paleo‐elevation changes.